Analisis Faktor Yang Berhubungan Dengan Tingkat Kepuasan Customer Akan Mutu Layanan Instalasi Radiologi RSUD Sidoarjo - R.Moh. Halil (Poltekkes Kemenkes Semarang, 2022)
Background: Radiology is a medical service that uses all radiation energy modalities for diagnosis and therapy, including imaging techniques and the use of X-ray radiation emission, radioactive, ultrasound, and electromagnetic radiofrequency. The quality of health services is closely related to the results of health services, both medically and non-medically. The purpose of the study is to find out the factors related to the level of customer satisfaction with the quality of radiological installation services of Sidoarjo Hospital.Methods: Design observational research with a cross-sectional approach. The population of all radiology guests at Sidoarjo Hospital in East Java in January, February and March amounted to 3,439 respondents. Samples of radiology guests at Sidoarjo Hospital in East Java amounted to 358 respondents with purposive sampling techniques. Independent variables of payment method or type of insurance, social status and trust. Dependent variable is the level of customer satisfaction with the quality of service. The analysis used is univariate, bivariate and multivariate analysis.Results: The results showed that there is a relationship between payment methods or types of insurance with the level of customer satisfaction with the quality of radiological installation services of Sidoarjo Hospital (p = 0.036). There is a social status relationship with the level of customer satisfaction with the quality of radiological installation services of Sidoarjo Hospital (p =0.048). There is a relationship of patient trust with the level of customer satisfaction with the quality of radiological installation services of Sidoarjo Hospital (p = 0.000). There are factors related to the level of customer satisfaction with the quality of radiological installation services of Sidoarjo Hospital which has an effect is satisfaction with a significance level of p = 0.000 and B = 0.150.Conclusions: This research is expected to increase knowledge or input and consideration in research related to the level of customer satisfaction with the quality of radiology installation services.